Disconnection notice: Exploring the internal effects of energy deprivation as a form of oppression - Lumagbas, Matthew Joel P. (Animo Repository, 2022)
This project is an absurdist short film about an unemployed woman’s struggle with the rise of electricity bills during a pandemic. Over time, she becomes increasingly burdened with sustaining her basic needs amidst the state of forced isolation and unemployment. This leads her down a state of energy deprivation that degrades her physical, moral, and mental state of being, which in turn forces her to resort to desperate measures. The story takes on the form of a psychological drama in order to flesh out the psychological implications of class struggle and deprivation. The film also adapts an absurdist approach to emphasize the futility of the character’s efforts in trying to escape her extreme situation. This project does not intend to use poverty porn or romanticize the struggles of hardship. It simply intends to show a harsh reality that is experienced by many. Inspired by the experience of the rise of electricity and other basic needs in the middle of a pandemic, the film stems from both our own personal experiences, and from the experiences of interviewed subjects across different classes.